Posthumous Culture of Montenegrins on a Timeline between Past and Present : The Pattern of Behavior - Medojevic, Milena (Ethnographica et Folkloristica Carpathica, 2023)
Montenegro is a country with a valuable and long tradition of everything related to life, especially death. Posthumous culture is remarkably detailed and significant for the people, most importantly in the earlier period when it represented the only foundation that held society together in difficult historical moments. This type of partially morbid way of self-expression of people has its roots in the deep and troubled past, often difficult and cruel to the inhabitants of Montenegro. The attention was pointed at the many traditional aspects, unwritten rules, and customs different from place to place, but in general, preserving the same function. From the type of clothes for the deceased, the eulogies uttered at the gravesite, to the male and female roles at the commemorations – the article handles the typical funeral processes. The aim of this paper is to acquaint the reader with the manner of behaviour of the Montenegrins towards the phenomenon that occurs when a person in the community dies and how a typical family handles the situation. For the sake of the research, interviews with two subjects providing their own perspectives were conducted. The significance of the study is personified by the sometimes contradictory stances of the people on death and the inevitable merging of secular and religious life.